Active flow control for interaction noise reduction of contra-rotating open rotors - Rinie A. D. Akkermans and Arne Stuermer and Jan Werner Delfs (AIAA Journal, 2016)
A possible way to decrease interaction tone noise of a contra-rotating open rotor is through the application of trailing-edge blowing by reducing the momentum deficit of the front rotor wake, and therefore its interaction with the aft rotor. In this contribution, an assessment of front-rotor trailing-edge blowing is presented for the reduction of contra-rotating open-rotor interaction noise. For this purpose, the German Aerospace Center designed a generic contra-rotating open rotor that has been modified to include trailing-edge blowing at the front rotor blades. With the German Aerospace Center computational fluid dynamics code TAU, unsteady Reynolds-averaged Navier-Stokes simulations have been made of the baseline and the trailing-edge blowing configuration. Subsequently, an aeroacoustic analysis has been performed with the Ffowcs-Williams/Hawkings tool APSIM+ for both configurations. The results show negligible differences of the aerodynamic performance, with significantly lower unsteady loading of the aft rotor when the trailing-edge blowing technique is active. The aeroacoustic results illustrate that the interaction tones are notably ameliorated; that is, a reduction over almost the complete polar angle is seen when trailing-edge blowing is active. With respect to the A-weighted overall sound pressure level, a reduction of approximately 2.5 dBA in the maximum level for the trailing-edge blowing configuration is achieved for the considered geometry. Noise reductions up to 5 dBA are displayed in the up-and downstream directions, which mainly arise from reduced interaction tones caused by the trailing-edge blowing technique. The decreased noise radiation with trailing-edge blowing mainly stems from a reduction in the first two interaction tones.